Evaluation of postoperative chronic neuropathic pain in patients with Lichtenstein hernia repair and laparoscopic hernia repair - Erol, Mehmet Fatih; Doğangün, Muhammed; Demir, Berkay; Arıcı, Sinan; Gözen, Füsun (The European Research Journal, 2025)
Objectives: The high incidence of inguinal hernia over the globe makes hernia repair the most common procedure in general surgery, and 10-15% of all surgeries are composed of hernia repair. In this study, we tried to elucidate the effect of risk factors of laparoscopic techniques on chronic neuropathic pain formation in the postoperative period in patients who underwent Lichtenstein hernia repair and laparoscopic hernia repair. Methods: A total of 404 patients have been enrolled in this study. Two different surgery techniques have been conducted on the participants, as Lichtenstein repair (n=214) and laparoscopic inguinal hernia repair (n=190). Demographic data of the patients were recorded. Transabdominal preperitoneal (TAPP) and totally extraperitoneal (TEP) techniques were applied to patients who underwent laparoscopic repair. The ’Lanss Pain Score’ was utilized in the evaluation of chronic pain in the postoperative period. Results: We detected a statistically significant difference between the groups in terms of age and the Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) scores (P<0.05). It was determined that the mean age of the patients with Lichtenstein repair was 57, and the mean LANSS score was 3. It was determined that the mean age of the patients with laparoscopic inguinal hernia repair was 49, and the mean LANSS score was 1. The distribution of demographic and clinical findings of the patients who underwent laparoscopic inguinal hernia repair according to the operation methods revealed no statistically significant difference in patients who underwent TAPP and TEP methods. Conclusions: In conclusion, the TEP and TAPP methods have lower pain in the postoperative period.